ChemInform Abstract: An Inverse Electron‐Demand Diene‐Transmissive Hetero‐Diels—Alder Reaction of N‐Sulfonyl‐[3]‐1‐azadendralenes for Stereocontrolled Synthesis of Polyhydroquinolines. Issue 50 (December 2015) - Kanai, Kan; Kobayashi, Satoru; Kudo, Kenji; Honjo, Takuya; Otani, Takashi; Saito, Takao
Abstract: The hetero‐Diels—Alder reaction of azatrienes (I) with vinyl ethers proceeds with high regio‐ and stereoselectivity to give cycloadducts (III).